2023
DOI: 10.1021/acsnano.3c05810
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Pt-Based Alloy Electrocatalysts for Improved Hydrogen Evolution Performance in Alkaline Electrolytes: A Comprehensive Review

Guoliang Gao,
Guang Zhu,
Xueli Chen
et al.

Abstract: The splitting of water through electrocatalysis offers a sustainable method for the production of hydrogen. In alkaline electrolytes, the lack of protons forces water dissociation to occur before the hydrogen evolution reaction (HER). While pure Pt is the gold standard electrocatalyst in acidic electrolytes, since the 5d orbital in Pt is nearly fully occupied, when it overlaps with the molecular orbital of water, it generates a Pauli repulsion. As a result, the formation of a Pt−H* bond in an alkaline environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 179 publications
0
9
0
Order By: Relevance
“…Pt-based materials hold significant potential in energy-related electrocatalytic applications, including HER, hydrogen oxidation reaction, alcohol oxidation reaction, oxygen reduction reaction, etc . Herein, we use the HER as a representative reaction to elucidate the impact of Te vacancy structures on the catalytic performance of PtTe materials.…”
Section: Resultsmentioning
confidence: 99%
“…Pt-based materials hold significant potential in energy-related electrocatalytic applications, including HER, hydrogen oxidation reaction, alcohol oxidation reaction, oxygen reduction reaction, etc . Herein, we use the HER as a representative reaction to elucidate the impact of Te vacancy structures on the catalytic performance of PtTe materials.…”
Section: Resultsmentioning
confidence: 99%
“…The commercial Ir/Ru- and Pt-based precious metal catalysts have excellent semireactive electrocatalytic effects for the OER and HER, respectively, , but high cost and limited abundance hinder their wide applications. , Many research works have demonstrated that alloying by incorporating other transition metals can reduce the relative content of precious metals in the catalyst to cut down cost, and the electrocatalytic performance can be improved by the adjustment of the electronic structures and surface properties. , Particularly in recent years, manufacturing surface defect lattices on the alloy catalyst is emerging as a great potential for boosting electrocatalytic HER and OER activities, because it can effectively adjust the charge distribution, molecular orbital hybridization, active center on the surface, and the adsorption of reactants. For instance, by mixing different defective structures into the atomic thin CoSe 2 nanoband, Fe doping and Co vacancy jointly optimized the electron states, so the binding energy of OH* was greatly reduced, achieving high catalytic OER activity. The high concentration defects in Mo 1– x Nb x Se 2 nanoparticles can significantly enhance HER performance, because they become the catalytic active sites and are conducive to the adsorption of H atoms. A large number of defects can be produced on the RhCu NTs surface after pickling, which promotes the transfer of electrons and adsorption of reactants, thus improving the electrocatalytic performance. Sial et al reported that a number of additional active edge sites can be provided on the multishell hollow NiCoFe alloy balls with defects to improve HER activity. In consequence, it may obtain unexpected high HER and OER activities by developing new alloy catalysts rich in defects.…”
Section: Introductionmentioning
confidence: 99%
“…Platinum (Pt) group nanostructures play a central role in renewable energy devices such as fuel cells, hydrogen-generating electrolyzers, and metal–air batteries. 1–5 However, their activity and stability depend closely on their micromorphology ( e.g. , dimensions, size, pore structure), 6–9 crystal phase ( e.g.…”
Section: Introductionmentioning
confidence: 99%